Measurement of consumption of sevoflurane for short pediatric anesthetic procedures: Comparison between dion's method and dragger algorithm - Preet Mohinder Singh; Anjan Trikha; Renu Sinha; Anuradha Borle (Wolters Kluwer Medknow Publications, 2013)
Background: The most common drugs used in an operating room are the "Inhalation agents" for maintenance of anesthesia yet their measurement methods during the procedure are not well-validated. Conventional methods of measuring the vaporizer weight after each use suffers from practical limitations of high error and time constraints. Aims: We compared two alternative methods available (Dion's method and Drager Inc. patent protocol) for their degree of concordance and correlation in real-time consumption of sevoflurane for pediatric procedures. Methodology: One hundred pediatric patients scheduled for ophthalmological examination under anesthesia were included in the study. Anesthesia was induced and maintained using sevoflurane with oxygen and nitrous oxide (1:1) on Primus workstation (Drager Inc., Germany). Total sevoflurane consumed for each procedure was calculated using Dion's equation and the values obtained from Drager Primus were noted and compared. Results: Both methods showed a very strong correlation (0.895 [P < 0.001]). Dion's method underestimated consumption by 2.59 ml with limits of agreement between 5.188 ml and −0.008 ml. Both test results showed a strong correlation, but poor concordance. Conclusions: Dion's method strongly correlates with Drager protocol although concordance between the two methods for measuring anesthetic gas consumption is poor. Dion's method underestimates the consumption and with slight modification addressing this underestimation, it can be electronically incorporated in other workstations to overcome limitations of real-time measurement of inhalation agent consumption.